Futuristic Costume Analysis of Arka Character (Case Study of "Arka" Animation) (Architecture Image Studies, 2025)
The term "futuristic" is used to describe a perspective on the future or a vision for what the world will be like in the future. It is impossible to predict what the future will be like with absolute certainty; however, it is possible to experience it as it becomes increasingly apparent in various fields, such as technology, design, and socio-cultural thought. This concept can serve as a foundation for the design of animations that employ a future-oriented narrative, integrating factual elements from the present. Arka is a 2D animation that employs the theme of the future and discusses the issue of stunting that takes place in one of the cities in Indonesia. The roles of characters in animation are the key to representing and conveying the message of the story to the audience. The objective of this research is to ascertain the costume concept employed in the design of an animated character set in the future. The research method used is a descriptive qualitative method. This qualita-tive research employs a case study approach with a review design analysis based on the Manga Matrix theory to provide a more detailed picture of the research ob-ject. The findings of this research suggest that a variety of creative and imagina-tive things can be used in the development of animated character designs that tell stories about futuristics.